Аналіз технологічного процесу сушки трав’яних кормів - Постнікова, Марина Вікторівна; Постникова, Марина Викторовна; Postnikova, Marina; Шарапов, О. (My University, 2018)
UK: Проведений аналіз технологічного процесу сушки трав’яних кормів, розглянуті питання енергетики процесу сушки кормів, виявлені основні фактори, які впливають на процес сушки. EN: The analysis of technological process of drying of grassy forages is carried out, questions of power engineering of process of drying of forages are considered, the basic factors which influence process of drying are revealed.
Keywords: трав’яні корми; активне вентилювання кормів; енергетика сушки; динаміка процесу; режими сушки; сушильне обладнання; herbal forages; active feed ventilation; drying energy; process dynamics; drying regimes; drying equipment